European Union in the Face of Russian Aggression against Ukraine (2014–2023) - Willa, Rafał; Płonka, Jakub (Historia i Polityka, 2024)
In 2014, Russia – despite denying it – began the first stage of the conflict in Ukraine by military occupation of a part of Ukraine’s territory. The European Union as an entity that wants to be considered one of the key participants in international relations could not leave this without reaction, especially since the events took place in its immediate neighbourhood and constituted an obvious violation of international law. Therefore, sanctions and restrictions were imposed on Russia hoping that they would trigger some reflection in the Kremlin. Nothing of the sort happened, so in 2022, Russia started the second stage of the conflict intended to seize further Ukrainian territories and place a government in Kiev that would be obedient to Moscow. This time the EU’s reaction was slightly different. This article is an attempt to familiarize the reader with EU activities regarding the Ukrainian conflict.